STRATEGI GURU DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS DARING DI SMP BRAWIJAYA SMART SCHOOL KOTA MALANG - Ramadhan Ramadhan; Azhar Haq; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This study aims to (1) describe online-based PAI learning strategies, (2) describe factors that inhibit and support online PAI learning strategies during the COVID-19 pandemic at SMP Brawijaya Smart School. The results of the study show that (1) online-based PAI learning strategies are to arrange planning, semester programs and lesson plans. This strategy is supported by the use of video and power point media that previously provided training for students and teachers using Microsoft Teams. (2) The factors that hinder the online-based PAI learning strategy during the COVID-19 pandemic include internal school factors, namely teacher activities outside of the online lack of communication between subject matter teachers and other teachers. Externally it comes from the students themselves who are less motivated and have uneven understanding of students, unstable network problems, and lack of attention from parents. Meanwhile, the supporting factors for online-based PAI learning strategies are school facilities and infrastructure and the ability of teachers to provide good understanding and knowledge. easy for students to understand like using Microsoft Team.